Tax evasion and competition - Laszlo Goerke; Marco Runkel (Center for Economic Studies and ifo Institute (CESifo), 2007)
Using a Cournot oligopoly model with an endogenous number of firms and evasion of indirect taxes, this paper shows that more intense competition may have the negative side-effect of eroding tax revenues by increasing tax evasion. This will be the case if market entry costs decrease. A similar result will hold if marginal production costs fall and demand is either weakly concave or convex and inelastic. The desirable result of more competition, less evasion and higher tax revenues will be obtained if (a) marginal production costs fall and demand is convex and elastic or (b) the demand elasticity increases.
Keywords: H25; H26; L13; L51; 330; Steuerflucht; Wettbewerb; Oligopol; Indirekte Steuer; Steueraufkommen; Theorie